Chinese 'low-tar' cigarettes do not deliver lower levels of nicotine and carcinogens. Issue 5 (27th May 2010) - Gan, Quan; Lu, Wei; Xu, Jiying; Li, Xinjian; Goniewicz, Maciej; Benowitz, Neal L; Glantz, Stanton A
Abstract : Background: Low-tar cigarette smoking is gaining popularity in China. The China National Tobacco Corporation (CNTC) promotes low-tar cigarettes as safer than regular cigarettes. Methods: A total of 543 male smokers smoking cigarettes with different tar yields (15 mg, regular cigarettes, 10–13 mg low-tar cigarettes and <10 mg low-tar cigarettes) were recruited in Shanghai, China, who then completed a questionnaire on smoking behaviour and provided a urine sample for analysis of the nicotine metabolites cotinine and trans-3′-hydroxycotinine. A total of 177 urine samples were selected at random for the analysis of the carcinogens polycyclic aromatic hydrocarbon metabolites (PAHs) (1-hydroxypyrene, naphthols, hydroxyfluorenes and hydroxyphenanthrenes) and the tobacco specific nitrosamine 4-(methylnitrosamino)-1-(3-pyridyl)-butanone (NNK) metabolites, 4-(methylnitrosamino)-1-(3-pyridyl)-butanol (NNAL) and NNAL-glucuronide. Values were normalised by creatinine to correct for possible distortions introduced by dilution or concentration of the urine. Results: Smokers of low-tar cigarettes smoked fewer cigarettes per day (p=0.001) compared to smokers of regular cigarettes. Despite this lower reported consumption, levels of cotinine, trans-3′-hydroxycotinine and PAHs in urine of people smoking low-tar cigarettes were not correlated with nominal tar delivery of the cigarettes they smoked. Urine concentrations of NNAL were higher in smokers of lower tar than higher tar cigarettes. Conclusions: Chinese low-tar cigarettes do not deliver lower doses of nicotine and carcinogens than regular cigarettes, therefore it is unlikely that there would be any reduction in harm. CNTC's promotion of low-tar cigarettes as 'less harmful' is a violation of the World Health Organization Framework Convention on Tobacco Control, which China ratified in 2005.